Pengembangan Pembelajaran Materi Qur’an Hadist Integratif Ekspositori dan Inquiri di SMA - Akmal; Fadriati (PT. Pusmedia Group Indonesia, 2024)
One of the factors that determine the achievement of educational goals is learning. Good learning can have a positive influence on students. Among the learning models that can be an alternative is learning based on an integrative expository and inquiry approach. The purpose of this learning model is for students to be able to integrate religious material with science, and have an inclusive, moderate, tolerant and respectful personality. This goal is very important because Indonesia is a sea of diversity in ethnicity, language, customs and religion. Learning through an integrative-expository and inquiry approach can be implemented in the Qur'an Hadith at Senior High School (SMA). Al-Qur'an Hadith is an important subject because it is related to the sources of Islam. In addition, high school students have begun to think critically, and can be brought into an integrative learning model of expository and inquiry. Keywords: Learning Development; Qur'an Hadith; Integrative Expository; Inquiry